Growth, Poverty and Inequality : Eastern Europe and the Former Soviet Union - Alam, Asad (Washington, DC: World Bank, 2012)
While the countries of Eastern Europe and the Former Soviet Union have made significant progress in reducing poverty in the past five years, poverty and vulnerability remain significant problems. More than 60 million are poor and more than 150 million are vulnerable. Growth, Poverty, and Inequality examines these important issues and recommends that public policies focus on: accelerating shared growth and job creation; improving public service delivery; strengthening social protection; and enhancing the monitoring of progress in poverty reduction. This book will be informative for policy makers and social scientists working in the Region.